EARLY ENGLISH LANGUAGE INSTRUCTION IN PRESCHOOL INSTITUTIONS OF UZBEKISTAN: CHALLENGES AND PEDAGOGICAL STRATEGIES (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
In this study, the current state of preschool education in Uzbekistan, which is in the process of implementing reforms in the field of education, was studied. The study outlines the primary obstacles faced in establishing English as the primary medium of instruction in preschool settings and elucidates effective pedagogical strategies that promote children's communicative development. The research results emphasize the importance of game-based teaching, teacher training, and multidisciplinary methods for the development of the meaningful impact of language in early childhood.